Type 1 diabetes linked PTPN22 gene polymorphism is associated with the frequency of circulating regulatory T cells - Milla Valta; Ahmad Mahfuz Gazali; Tyyne Viisanen; Emmi‐Leena Ihantola; Ilse Ekman; Jorma Toppari; Mikael Knip; Riitta Veijola; Jorma Ilonen; Johanna Lempainen; Tuure Kinnunen (Wiley, 2022)
Dysfunction of FOXP3‐positive regulatory T cells (Tregs) likely plays a major role in the pathogenesis of multiple autoimmune diseases including type 1 diabetes (T1D). Whether genetic polymorphisms associated with the risk of autoimmune diseases affect Treg frequency or function is currently unclear. Here, we analysed the effect of T1D‐associated major HLA class II haplotypes and seven single nucleotide polymorphisms in six non‐HLA genes [INS (rs689), PTPN22 (rs2476601), IL2RA (rs12722495 and  rs2104286), PTPN2 (rs45450798), CTLA4 (rs3087243), and ERBB3 (rs2292239)] on peripheral blood Treg frequencies. These were determined by flow cytometry in 65 subjects who had progressed to T1D, 86 islet autoantibody‐positive at‐risk subjects, and 215 islet autoantibody‐negative healthy controls. The PTPN22 rs2476601 risk allele A was associated with an increase in total (p = 6 × 10−6) and naïve (p = 4 × 10−5) CD4+CD25+CD127lowFOXP3+ Treg frequencies. These findings were validated in a separate cohort comprising ten trios of healthy islet autoantibody‐negative children carrying each of the three PTPN22 rs2476601 genotypes AA, AG, and GG (p = 0.005 for total and p = 0.03 for naïve Tregs, respectively). In conclusion, our analysis implicates the autoimmune PTPN22 rs2476601 risk allele A in controlling the frequency of Tregs in human peripheral blood.